(untitled) (International Journal of Engineering and Computer Science, 2018)
The main aim of this paper is to provide voice to voiceless people with the help of Smart Gloves. With the proposed work, sign language is converted into speech using accelerometer and microcontrollers. where it reduces the communication barrier between two communities using the smart gloves